That's not natural! Consumer response to disconfirmed expectations about 'natural' food. (1st January 2023) - Schirmacher, Helena; Elshiewy, Ossama; Boztug, Yasemin
Abstract: Natural claims on food products create a large number of positive expectations. This research aims to reveal which potentially disconfirmed expectations about 'natural' food are problematic as they harm consumer attitudes and intentions. In a pre-study (N = 160), we show that consumers expect natural-claimed food to be organic, locally produced, minimally processed, fresh, to ensure better animal welfare, and to be free from GMO, artificial ingredients, antibiotics, and hormones. In our main study (N = 2152), we show that the natural claim increases purchase intention, mediated via brand trust and product attitude. However, when consumers learn that their expectations may be disconfirmed, their brand- and product-related attitudes decrease, which in turn leads to reduced purchase intentions. These findings imply that food marketers can profit from the natural claim, but that there is a large potential for irresponsible food marketing and consumer deception, which can result in negative expectation disconfirmation. We also inform policy makers which product expectations should be considered for consumer protection against halo effects induced by the natural claim. Regulation or education about the meaning of the claim can help consumers to make more informed decisions.